Screening and identification of critical transcription factors involved in the protection of cardiomyocytes against hydrogen peroxide-induced damage by Yixin-shu. Issue 1 (December 2017) - Zhang, Jingjing; Geng, Ya; Guo, Feifei; Zhang, Fangbo; Liu, Mingwei; Song, Lei; Ma, Yuexiang; Li, Defeng; Zhang, Yi; Xu, Haiyu; Yang, Hongjun
Abstract Oxidative stress initiates harmful cellular responses, such as DNA damage and protein denaturation, triggering a series of cardiovascular disorders. Systematic investigations of the transcription factors (TFs) involved in oxidative stress can help reveal the underlying molecular mechanisms and facilitate the discovery of effective therapeutic targets in related diseases. In this study, an integrated strategy which integrated RNA-seq-based transcriptomics techniques and a newly developed concatenated tandem array of consensus TF response elements (catTFREs)-based proteomics approach and then combined with a network pharmacology analysis, was developed and this integrated strategy was used to investigate critical TFs in the protection of Yixin-shu (YXS), a standardized medical product used for ischaemic heart disease, against hydrogen peroxide (H2 O2 )-induced damage in cardiomyocytes. Importantly, YXS initiated biological process such as anti-apoptosis and DNA repair to protect cardiomyocytes from H2 O2 -induced damage. By using the integrated strategy, DNA-(apurinic or apyrimidinic site) lyase (Apex1), pre B-cell leukemia transcription factor 3 (Pbx3), and five other TFs with their functions involved in anti-oxidation, anti-apoptosis and DNA repair were identified. This study offers a new understanding of the mechanism underlying YXS-mediated protection against H2 O2 -induced oxidative stress in cardiomyocytes and reveals novel targets for oxidative stress-related diseases.